(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This study evaluates improved diagnostic and surgical strategies for pediatric echinococcosis, demonstrating the effectiveness of combined imaging and serology, and the benefits of minimally invasive techniques. Findings support stage-specific surgical algorithms that enhance safety, reduce complications, and provide practical guidance for optimizing outcomes in children with this parasitic disease.